2010
DOI: 10.1063/1.3475564
|View full text |Cite
|
Sign up to set email alerts
|

Global potential energy surfaces for O(P3)+H2O(A11) collisions

Abstract: Global analytic potential energy surfaces for O((3)P) + H(2)O((1)A(1)) collisions, including the OH + OH hydrogen abstraction and H + OOH hydrogen elimination channels, are presented. Ab initio electronic structure calculations were performed at the CASSCF + MP2 level with an O(4s3p2d1f)/H(3s2p) one electron basis set. Approximately 10(5) geometries were used to fit the three lowest triplet adiabatic states corresponding to the triply degenerate O((3)P) + H(2)O((1)A(1)) reactants. Transition state theory rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Moreover, Conforti et al [99] found good agreement with molecular beam measurements [101] of the relative cross section in reaction (R13). Due to significant disagreement of the theoretical studies [33,[97][98][99][100] the uncertainty of this rate constant is evaluated to be of a factor of 5. In the previous model [6] the recommendation of Baulch et al [67] for the rate constant of reaction (ÀR14) was adopted.…”
Section: Reactionsmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, Conforti et al [99] found good agreement with molecular beam measurements [101] of the relative cross section in reaction (R13). Due to significant disagreement of the theoretical studies [33,[97][98][99][100] the uncertainty of this rate constant is evaluated to be of a factor of 5. In the previous model [6] the recommendation of Baulch et al [67] for the rate constant of reaction (ÀR14) was adopted.…”
Section: Reactionsmentioning
confidence: 76%
“…with the rate constant calculated by Conforti et al [99]. Their modeling results were preferred to other works [97,98,100] since the rate constant of the channel…”
Section: Reactionsmentioning
confidence: 93%
“…However, for ozone at a water interface, this photolytic pathway becomes relevant because the reaction of O( 3 P) with water to form two OH radicals is energetically accessible in the Chappuis band region. This reaction has been investigated in the literature (26,27) but to get very accurate energy values, we have revisited the process by performing geometry optimizations at the quadratic configuration interaction level with single and double excitations (QCISD) using the aug-cc-pVTZ basis set, and carrying out single-point energy calculations at the coupled cluster level with a full treatment of single and double excitations and a perturbative correction for triple excitations [CCSD(T)] extrapolated to the complete basis set (CBS) limit. as N 2 , O 2 , or CO 2 ) and only a small fraction of O( 1 D) reacts with water or methane to form OH radicals, according to reactions 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…At these energies, several reactions occur: [2][3][4][5] OH formation: O( 3 P) + H 2 O(X, 1 Studies of O( 3 P) + H 2 O( 1 A 1 ) hyperthermal collisions go back nearly 40 years to measurements of infrared radiation in shock tubes. 6 In the 1980s, cross sections for vibrational excitation were calculated using quasi-classical trajectory (QCT) methods 7 on a global non-reactive potential surface.…”
Section: Introductionmentioning
confidence: 99%
“…In a second series of calculations, the recently developed O( 3 P) + H 2 O( 1 A 1 ) surfaces of Ref. 3 were used, including all reactive channels (Eqs.…”
Section: Introductionmentioning
confidence: 99%